2018
DOI: 10.1029/2018gl079647
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the 128‐ka Antarctic Climate Response to Northern Hemisphere Ice Sheet Melting Using the Isotope‐Enabled HadCM3

Abstract: Warmer than present Antarctic and Southern Ocean temperatures during the last interglacial, approximately 128,000 years ago, have been attributed to changes in north‐south ocean heat transport, causing opposing hemispheric temperature anomalies. We investigate the magnitude of Antarctic warming and Antarctic ice core isotopic enrichment in response to Northern Hemisphere meltwater input during the early last interglacial. A 1,600‐year HadCM3 simulation driven by 0.25 Sv of meltwater input reproduces 50–60% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 48 publications
4
35
1
Order By: Relevance
“…demonstrated that the distinctive peak in d 18 O observed in Antarctic ice cores at 128 ka was likely due to the loss of winter sea ice in the Atlantic, Indian, and Pacific sectors of the Southern Ocean. To achieve this winter sea ice extent required forcing by the H11 meltwater event (Holloway et al, 2017(Holloway et al, , 2018. The CMIP6-PMIP4 Tier 2 LIG 590 experiments (lig127k-H11, lig127-gris, lig127k-ais) will allow modeling groups to explore the effects of the H11 meltwater event and the Antarctic and Greenland ice sheets at their minimum LIG extent and lower elevations (Otto-Bliesner et al, 2016).…”
mentioning
confidence: 99%
“…demonstrated that the distinctive peak in d 18 O observed in Antarctic ice cores at 128 ka was likely due to the loss of winter sea ice in the Atlantic, Indian, and Pacific sectors of the Southern Ocean. To achieve this winter sea ice extent required forcing by the H11 meltwater event (Holloway et al, 2017(Holloway et al, , 2018. The CMIP6-PMIP4 Tier 2 LIG 590 experiments (lig127k-H11, lig127-gris, lig127k-ais) will allow modeling groups to explore the effects of the H11 meltwater event and the Antarctic and Greenland ice sheets at their minimum LIG extent and lower elevations (Otto-Bliesner et al, 2016).…”
mentioning
confidence: 99%
“…1) was due to the loss of West antarctic ice, but concluded that it was extremely likely that the WaIS was largely still intact at 128 kyr BP. a recent extension of this work (Holloway et al 2018) using a fully coupled, isotope-enabled climate model demonstrates that the reconstructed penultimate deglacial meltwater event (around 0.2 Sv of meltwater input to the North atlantic region over around 4 kyr) appears to explain the peak at 128 kyr BP in δ 18 O, via the well-known bipolar seesaw mechanism; these results indicate that meltwater input over ~3600 years can generate the whole ice-core δ 18 O signal at 128 kyr BP ( Fig. 2a).…”
Section: Selmentioning
confidence: 71%
“…Carlson 2 and M. Holloway 1,3,4 doi.org/10.22498/pages.27.1.14 Figure 2. SCIENCE HIGHLIGHTS: Paleo CoNstraiNts oN sea-level rise all of these aspects exert a strong and readily identifiable influence on δ 18 O at the antarctic ice-core sites (Holloway et al 2016(Holloway et al , 2018. Holloway et al (2016) investigated whether the distinctive peak in δ 18 O observed in ice cores at ~128 kyr BP ( Fig.…”
Section: Selmentioning
confidence: 99%
“…1) was due to the loss of West Antarctic ice, but concluded that it was extremely likely that the WAIS was largely still intact at 128 kyr BP. A recent extension of this work (Holloway et al 2018) using a fully coupled, isotope-enabled climate model demonstrates that the recon structed penultimate deglacial meltwater event (around 0.2 Sv of meltwater input to the North Atlantic region over around 4 kyr) appears to explain the peak at 128 kyr BP in δ 18 O, via the well-known bipolar seesaw mechanism; these results indicate that melt water input over ~3600 years can generate the whole ice-core δ 18 O signal at 128 kyr BP (Fig. 2a).…”
mentioning
confidence: 81%